Mempelajari Sifat Introversi-Ekstraversi Remaja, Kebutuhan Akan Rasa Memiliki dan Kegemaran dalam Jejaring Sosial Siswa SMA Darul 'Ulum Kepohbaru (Jurusan Bimbingan dan Konseling Islam, 2021)
The purpose of this study is to gain an understanding of the relationship between introverted-extrovert personality traits, the need for a sense of belonging and the intensity of the use of social networks in Darul Ulum Kepohbaru Senior High School. The data analysis technique used in this research is quantitative with descriptive analysis, and test. The data instrument used to collect data in this study was to use 3 scales, namely Facebook Intensity Scale, Introvert and Extrovert Scale, Need to Belongingness Scale. The number of subjects or samples in this study were 100 students who were in the senior high school (SMA) Darul Ulum Kepohbaru. Based on the results of the study, it can be concluded that the students from SMA Darul Ulum Kepohbaru who were sampled in the study were able to balance their extrovert-introvert nature, and had a good need for belonging, this made them prefer to interact directly with other people. and they don't use social networks very often to connect with other people. so that it an be said that they have a balanced introvert-extrovert nature, need to belongingness, and indulgence in social networking.